Visual Surround Suppression in Schizophrenia - Tibber, Marc S.; Anderson, Elaine J.; Bobin, Tracy; Antonova, Elena; Seabright, Alice; Wright, Bernice; Carlin, Patricia; Shergill, Sukhwinder S.; Dakin, Steven C. (Frontiers in Psychology, 2013)
Compared to unaffected observers patients with schizophrenia show characteristic differences in visual perception, including a reduced susceptibility to the influence of context on judgements of contrast - a manifestation of weaker surround suppression. To examine the generality of this phenomenon we measured the ability of 24 individuals with schizophrenia to judge the luminance, contrast, orientation and size of targets embedded in contextual surrounds that would typically influence the target’s appearance. Individuals with schizophrenia demonstrated weaker surround suppression compared to matched controls for stimuli defined by contrast or size, but not for those defined by luminance or orientation. As perceived luminance is thought to be regulated at the earliest stages of visual processing our findings are consistent with a suppression deficit that is predominantly cortical in origin. In addition, we propose that preserved orientation surround suppression in schizophrenia may reflect the sparing of broadly tuned mechanisms of suppression. We attempt to reconcile these data with findings from previous studies.